BIOBUSINESS X CITIES:: Amazonian challenges in the context of a new economic development matrix - Silva, Michele Lins Aracaty e (2024)
the current development model implemented in Amazonas does not make representative use of Amazonian biodiversity products. Despite the wealth generated by the PIM, the region needs an alternative and complementary path to the export model that will explore regional potential and contribute to improving the living conditions of cities in the interior of the Amazon. We believe that exploring the bioeconomy through biobusinesses in interior cities is the most viable alternative for implementing a new economic development matrix, enabling a bridge between biodiversity and the wealth generated in the PIM. To this end, we aim to discuss the exploration of biobusinesses in the scenario of Amazonian cities with a focus on regional development. This is a qualitative, exploratory, descriptive research, using secondary material of the bibliographic and documentary type and content analysis. The current economic model has little or no connection with the forest and does not value biodiversity. The bioeconomy through biobusinesses will only be a viable alternative if we manage to improve infrastructure, telecommunications, mobility, health, safety and basic sanitation in interior cities so that they become attractive to investments and new brains